2018
DOI: 10.1111/jnc.14306
|View full text |Cite
|
Sign up to set email alerts
|

Genetic removal of eIF2α kinase PERK in mice enables hippocampal L‐LTP independent of mTORC1 activity

Abstract: Characterization of the molecular signaling pathways underlying protein synthesis-dependent forms of synaptic plasticity, such as late long-term potentiation (L-LTP), can provide insights not only into memory expression/maintenance under physiological conditions but also potential mechanisms associated with the pathogenesis of memory disorders. Here, we report in mice that L-LTP failure induced by the mammalian (mechanistic) target of rapamycin complex 1 (mTORC1) inhibitor rapamycin is reversed by brain-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 47 publications
(80 reference statements)
3
18
0
Order By: Relevance
“…Markedly, AD-associated eEF2 hyperphosphorylation was restored with selective AMPKα1, but not AMPKα2, suppression ( Figure 5A). To directly measure de novo protein synthesis, we used the surface sensing of translation (SUnSET, a nonradioactive puromycin end-labeling assay) on living acute hippocampal slices (42,43). In agreement with previous studies (44), de novo protein synthesis in hippocampal slices (assessed by puromycin labeling) was reduced in Tg mice as compared with WT controls ( Figure 5B).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Markedly, AD-associated eEF2 hyperphosphorylation was restored with selective AMPKα1, but not AMPKα2, suppression ( Figure 5A). To directly measure de novo protein synthesis, we used the surface sensing of translation (SUnSET, a nonradioactive puromycin end-labeling assay) on living acute hippocampal slices (42,43). In agreement with previous studies (44), de novo protein synthesis in hippocampal slices (assessed by puromycin labeling) was reduced in Tg mice as compared with WT controls ( Figure 5B).…”
Section: Resultssupporting
confidence: 83%
“…Tissues were removed from appropriate structures and flash frozen on dry ice. Tissues were then homogenized in an appropriate lysis buffer and quantified as previously described (43). Samples were loaded on 4% to 15% TGX Precast Gels (Bio-Rad) and transferred to nitrocellulose membranes.…”
Section: Figure 3 Suppression Of Ampkα Does Not Alter Ad-associated mentioning
confidence: 99%
“…Mounting evidence suggests an important role for elongation regulation in cognition, with recent studies linking dysregulation of elongation factors with AD pathophysiology (15,(44)(45)(46)(47). Of note, a recent study showed a connection between eIF2 signaling and eEF2 phosphorylation in neurons (48). While additional studies are warranted to evaluate ADassociated dysregulation of initiation and elongation separately, there is evidence for crosstalk between these 2 phases of translation via eIF2 and eEF2.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampus late long-term potentiation (L-LTP), inhibited by rapamycin acting on the mammalian target of rapamycin complex 1 (mTORC1), was reversed in the PERK KO mice. Mechanistically, the PERK KO mice displayed no alterations in mTORC1 signaling but showed reduced phosphorylation of eukaryotic elongation factor 2 (eEF2) with increased protein translation (Zimmermann et al, 2018 ). These results point to the role of PERK in mTORC1-independent L-LTP via its effects on eEF2-mediated translation.…”
Section: Perk Signalingmentioning
confidence: 99%